Kritiske bemærkninger til den officielle danske retskrivningsordbog - Tarp, Sven (LexicoNordica, 2002)
The main function of an orthographic dictionary is to assist users in solving problems related to written text production. The team behind the official orthographic dictionary of Danish, Retskrivningsordbogen, are fine linguists, but this is far from enough to guarantee a high-quality dictionary. Apparently, no serious analysis has been made of the users’ problems and real needs in terms of written text production and how lexicography can help solving these problems. The article argues that this might be the fundamental reason why Retskrivningsordbogen is a poor lexicographic product and provides a number of concrete proposals on how to approve it.